Given f(x) = k(2+x), find the value of k if f^-1 (-2) = -3

Expert Answers

An illustration of the letter 'A' in a speech bubbles

f(x) = k(2+x)

First we will rewrite:

y= k(2+ x)

Let us determine the inverse .

==> We will divide by k.

==> (x+2) = y/k

==> x =...

(The entire section contains 92 words.)

Unlock This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial
Approved by eNotes Editorial Team

Posted on